Cluster as an object of research in the institutional economy and accounting: square plates - Hyk, V. (Видавництво Львівської політехніки, 2020)
A critical analysis of globalization processes in the economy is considered and conducted, with an emphasis on the factors of increasing competition. It is established that due to the development of scientific and technological progress of new approaches to socioeconomic development requires the formulation of a new type of institutional environment. It is argued that an important tool for increasing the competitiveness of the economy are the processes of adaptive clustering. It is noted that in the Ukrainian national economy this approach has not become widespread and it is proved that an important component of inhibiting these processes is the lack of proper information base. It is proved that under such conditions an important role in information support belongs to the accounting system. The hypothesis of the study is the assumption that the creation of an accounting and information system in the management of cluster associations should be based on an institutional approach. From this conceptual approach, a study of the current state of accounting in the cluster, taking into account institutional theory. The purpose of the article is to clarify the disposition of accounting as a socio-economic institution and the formation of a cluster as a systemic institution. The existence of a slightly different nature of the interaction of these institutions is established, in which the role of the accounting information system is considered differently, in which it is considered in understanding the information network of the enterprise, and thus differs from the “traditional” interaction “accounting – enterprise”. The study identifies the main reasons for the need to use the provisions of institutional theory to address the problems of accounting in the cluster. Based on the study, we propose to consider pre-grouping these concepts (institutional theory, accounting, cluster) and divide them into separate planes: the impact of institutional theory on the development of accounting, cluster from the standpoint of institutional theory, institutional interaction between accounting and cluster.
Keywords: accounting; institutional theory; information network of communications; integrated structures; cluster; М41; L24; 657.01